Art, adolescence and Social Work: Anja, the invisible manager - González Abad, Libertad (Cuadernos de Trabajo Social, 2016)
This article has been written with the intention of being able to analyse the contributions of art —theatre, in this case— to the practice of social work. For this purpose, we have chosen to read the social reality in which we intervene through the lens of social constructionism. This helps us to rescue the social and subjective side of art, and, moreover, to recover the depathologization of the subject in professional intervention. Thus, using a practical case taken from work with adolescents in the German FSJ programme, hand-in-hand with a young girl called Anja we trace the developmental and sociological aspects of adolescence in order to later address certain common points of art and psychosocial work. Art will hence be redefined as a transitional object allowing questions to be addressed relating to (self-) perception, attachment, communication and changes in conduct as the ultimate goal of professional action. Lastly, we note the limitations and risks of art-based intervention, in order to conclude with a final synopsis.